Rebranding of Crispy Seasoned Flour Produced by UD. LIBAS to Improve The Product Quality - Yunus, Muhammad; Wibowo, Yuli; Nurhayati, N. (Faculty of Agricultural Technology, University of Jember, 2025)
Crispy chicken and crispy mushrooms are examples of processed products using crispy seasoned flour. There are many spice flour producers, from small, medium, and large to micro industries. UD. LIBAS is one of the producers of crispy seasoning flour on a home industry scale (MSMEs). This research aims to improve the quality of “IIBAS” crispy seasoned flour through product rebranding. The research stages that be carried out are the process of data collection, analysis, and interpretation to achieve the research objectives. The existing brand of crispy seasoning flour